Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have to prove $\vec x \perp \vec z$ and $\vec y \perp \vec z$ imply $\vec x || \vec y$ where $\vec x,\vec y,\vec z \in \mathbb{R}^2$ and $z$ nonzero.

I know $x \perp z \Leftrightarrow x_1z_1+x_2z_2=0$ and $y \perp z \Leftrightarrow y_1z_1+y_2z_2=0$. If two vectors are parallel, I can write $\vec x = \alpha \vec y$.

I tried to write $x_1z_1+x_2z_2=y_1z_1+y_2z_2$ but this didn't help me to find an $\alpha$ to satisfy $\vec x = \alpha \vec y$.

Anyone got a hint for me?

share|cite|improve this question
What is the vector space in the question ? – Belgi Apr 29 '13 at 10:10
I assume you're working in two dimensions here. For a three-dimensional space, your statement clearly doesn't hold, since $(1,0,0)$, $(0,1,0)$, $(0,0,01)$ are all perdendicular to each other... You might want to mention that in the question... – fgp Apr 29 '13 at 10:11
It's for $\mathbb{R}^2$, sorry – ulead86 Apr 29 '13 at 10:11
I added the condition that $z\neq 0$ since the statement is clearly false if $z=0$. – rschwieb Apr 29 '13 at 10:44
$z1,z2 \not=0 \to y_1x_1z_1+y_1x_2z_2-x_1y_1z_1-x_1y_2z_2=0 \to y_1x_2-x_1y_2=0 \to \dfrac{x_1}{y_1}=\dfrac{x_2}{y_2}=\alpha \to \vec x = \alpha \vec y$ – chenbai May 3 '13 at 3:31
up vote 4 down vote accepted

If $x=0$ then $y$ is degenerately parallel to $x$ in the sense that $0y=x$. We suppose now that $x\neq 0$.

Since $x$ and $z$ are nonzero and perpendicular, they form a basis for $\Bbb R^2$. That means it is possible to write $y=\alpha x+\beta z$ for some $\alpha, \beta\in \Bbb R$.

Now we check the inner product of $y$ with $z$ and use the given facts that $y\cdot z=0$ and $x\cdot z=0$:

$$0=y\cdot z=\alpha (x\cdot z) +\beta (z\cdot z)=0+\beta \|z\|^2$$

Since $z$ is nonzero $0=\beta\|z\|^2$ implies $\beta=0$. Thus in the original expression $y=\alpha x+0$ yields that $y$ is a scalar multiple of $x$.

share|cite|improve this answer
(+1) for a very simple proof. I enjoy reading proofs like this. Thanks. – BU982T Apr 29 '13 at 10:47

$\vec x\perp\vec z$: $x_1z_1+x_2z_2=0$

$\vec y\perp\vec z$: $y_1z_1+y_2z_2=0$

With matrix notation: $$\left( \begin{array}{cc} x_1&x_2\\ y_1&y_2 \end{array}\right)\cdot\left(\begin{array}{c} z_1\\ z_2 \end{array}\right)=\left(\begin{array}{c} 0\\ 0 \end{array}\right)$$

Suppose $\vec x,\vec y$ not parallel. Then the matrix is invertible, and this implies (multiply both sides by the inverse matrix) that $\vec z=0$, which I suppose is not the case.

share|cite|improve this answer

Hint: If $W$ is a vector subspace of a vector space $V$ then $$\dim(W^{\perp})=\dim(V)-\dim(W)$$ where $W^{\perp}$ is the set of all vectors in $V$ that are perpendicular to all the vectors in $W$

share|cite|improve this answer
good idea, but is it possible to find a proof without vector subspaces? – ulead86 Apr 29 '13 at 10:15
@ulead86 It is. – rschwieb Apr 29 '13 at 10:31

$\mathbb{R}^2$ is a flat two dimensional space. Therefore, any two vectors orthogonal to each other span an orthogonal basis in $\mathbb{R}^2$. Now choose, say, ${\vec e}_1 ={\vec x}$ and ${\vec e}_2 ={\vec z}$ as basis vectors for your $\mathbb{R}^2$. A basis of a flat space has the property that any vector in the space can be decomposed into components along the basis vectors (through a projection via scalar product). So that you can write:

$${\vec y}=\sum_{i=1}^2({\vec y}\cdot{\vec e}_i){\vec e}_i=({\vec y}\cdot{\vec x}){\vec x}+({\vec y}\cdot{\vec z}){\vec z}=({\vec y}\cdot{\vec x}){\vec x}=\alpha{\vec x}$$

share|cite|improve this answer

Solve your system $$\begin{align} x_1 z_1 + x_2 z_2 &= 0 \\ y_1 z_1 + y_2 z_2 &= 0 \end{align}$$ for $z_1$ and $z_2$, but note that $z_1$ and $z_2$ aren't both zero. You'll see, then, that there must be a relation between the $x_i$ and $y_i$; you can tease this relation into the form $x = \alpha y$. (Hint: If $pq-rs=0$, then $pq=rs=t$ for some $t$.)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.